« Les boucliers de paix » et les « boucliers de guerre » dans la littérature norroise : invention littéraire ou réalité matérielle ? - Simon Lebouteiller (Tabularia)
The legendary sagas and the chivalric sagas often mention the use by Scandinavian armies of a “war shield” (herskjöldr) and a “peace shield” (friðskjöldr), the first one symbolizing their warlike intentions and the second one being on the contrary a sign of their wish to stop fighting. These objects may be connected to the red and white shields mentioned in theses sources. It seems difficult to determine if this technic is real considering that these fiction texts describe fantasist representations about Nordic prehistory. However, we will see that similar stories in Russian and Frankish sources might suggest that shields had really been used as communication tools.